Smart sustainable water monitoring system via internet of things (IOT) for water retention pond UITM cawangan Johor, Kampus Pasir Gudang - Misnan, Mohamad Farid; M. Thamrin, Norashikin; Nik Ibrahim, Nik Nor Liyana (penerbit UTHM, 2022)
Water retention ponds developed in UiTM Pasir Gudang is used to accommodate the overflowed water from the campus facilities. Overflowed water is accumulated into this water retention pond and will flow to other water sources. Water from the water retention pond has potential to contaminate other water sources as well as the environment. To maintain the water retention pond, a sustainable water monitoring system with an integration of internet of things (IoT) technology is designed and implemented. A fully developed integrated IoT monitoring system is presented in this research paper. The developed system will assess the water parameter such as pH and water temperature as well as water quality to serve as the water health indicator. This system includes a pH sensor, temperature sensor, rain sensor, sustainable power supply, wireless frequency data transmission module, and IoT data acquisition system in the base station. After the water data process has been performed and verified, the authorities will be notified of the unhealthy water condition. The developed system also allows any person or authority to monitor the water quality in that environment from anywhere. As a result of the collected data for water data parameters, the developed system provides an efficient water parameter monitoring system. Thus, early actions can be taken to reduce any harmful effects to the environment due to poor intervention.